Microgrids: A Model for Basic Microsurgery Skills Training - Gunasagaran, Jayaletchumi; Rasid, R.J.; Mappiare, Sahrinanah; Devarajooh, Cassidy; Ahmad, Tunku Sara (Malaysian Orthopaedic Association, 2018)
Introduction: Microsurgery is a subspecialised field which requires high technical skill. Laboratory training offers good opportunity for novice surgeons to learn and repetitively practise their skills prior to hands-on clinical practice. Commonly, the training programme consists of models in a stepwise increase in fidelity: from latex sheet to anaesthetised rat. We introduce microgrids model as a daily warm up procedure in a 5-day basic microsurgery course. The purpose of this study is to evaluate the correlation between microgrids colouring under magnification with microsuturing proficiency among novice surgeons. Materials and Methods: Participants were required to fill in microgrids under magnification everyday during their 5-day training as a starter test. The number of completely filled in microgrids in 20 seconds was recorded. A simulated cut on latex sheet was sutured and the time taken to apply five sutures was recorded. The sutures were evaluated with modified Global Rating Scale (GRS). Data was analysed with SPSS. Results: There was a statistically significant correlation between the number of microgrids coloured and the time taken to apply five sutures (p<0.01). An increase in number of microgrids coloured was significantly associated with the increase in quality of the suturing technique (p< 0.01). During the 5-day basic microsurgery skills training for novice surgeons, microsuturing skill improvement correlated with microgrid colouring. Conclusion: Microgrids colouring reflected microsuturing proficiency. It is an inexpensive, readily available, and simple model of ‘warm up’ for hand dexterity. The microgrids model can function as a starter test for initial training and a quick screening measure to assess microsurgical skill.